Does Cannabis Extract Obtained From Cannabis Flowers With Maximum Allowed Residual Level of Aflatoxins and Ochratoxin a Have an Impact on Human Safety and Health? - Serafimovska, Tijana; Stefanovski, Sasho; Erler, Joachim; Keskovski, Zlatko; Stefkov, Gjoshe; Mitevska, Marija; Darkovska Serafimovska, Marija; Balkanov, Trajan; Tonic Ribarska, Jasmina (Frontiers in Medicine, 2021)
Aim: The aim of this study was to investigate whether the cannabis extract obtained from cannabis flowers that contains the maximum allowed level of mycotoxins affects the human safety and health Methods: Experimental design was done by adding maximum allowed concentration of aflatoxins (B1, B2, G1, G2) and ochratoxin A, according to Ph. Eur to cannabis flowers. The concentration of aflatoxins and ochratoxin A were determined after extraction with ethanol 96% in obtained decarboxylated extract by LC/MS/MS. Results: A novel LC/MS/MS method was developed and validated for determination of aflatoxins and ochratoxin A in cannabis extracts. The results obtained indicate that aflatoxins and ochratoxin A, primary added to the cannabis dried flowers, were also determined into the obtained final extract, in amounts 2 – 3 times higher (m/m) than in starting plant material. Conclusion: With this experiment we have shown that mycotoxins, especially aflatoxins-extremely toxic secondary metabolites, can reach critical values in cannabis extracts obtained from dry cannabis flowers with maximum allowed quantity of mycotoxins thus can cause harm on consumers health.